Staphylococcal enterotoxin A (SEA) stimulates STAT3 activation and IL-17 expression in cutaneous T-cell lymphoma - Willerslev-Olsen, Andreas; Krejsgaard, Thorbjørn; Lindahl, Lise M.; Litvinov, Ivan V.; Fredholm, Simon; Petersen, David L.; Nastasi, Claudia; Gniadecki, Robert; Mongan, Nigel P.; Sasseville, Denis; Wasik, Mariusz A.; Bonefeld, Charlotte M.; et al. (American Society of Hematology, 2016)
Cutaneous T-cell lymphoma (CTCL) is characterized by proliferation of malignant T cells in a chronic inflammatory environment. With disease progression, bacteria colonize the compromised skin barrier and half of CTCL patients die of infection rather than from direct organ involvement by the malignancy. Clinical data indicate that bacteria play a direct role in disease progression, but little is known about the mechanisms involved. Here, we demonstrate that bacterial isolates containing staphylococcal enterotoxin A (SEA) from the affected skin of CTCL patients, as well as recombinant SEA, stimulate activation of signal transducer and activator of transcription 3 (STAT3) and upregulation of interleukin (IL)-17 in immortalized and primary patient-derived malignant and nonmalignant T cells. Importantly, SEA induces STAT3 activation and IL-17 expression in malignant T cells when cocultured with nonmalignant T cells, indicating an indirect mode of action. In accordance, malignant T cells expressing an SEA-nonresponsive T-cell receptor variable region β chain are nonresponsive to SEA in monoculture but display strong STAT3 activation and IL-17 expression in cocultures with SEA-responsive nonmalignant T cells. The response is induced via IL-2 receptor common γ chain cytokines and a Janus kinase 3 (JAK3)-dependent pathway in malignant T cells, and blocked by tofacitinib, a clinical-grade JAK3 inhibitor. In conclusion, we demonstrate that SEA induces cell cross talk-dependent activation of STAT3 and expression of IL-17 in malignant T cells, suggesting a mechanism whereby SEA-producing bacteria promote activation of an established oncogenic pathway previously implicated in carcinogenesis.